Wildwood Park pavilion (Minnesota Streetcar Museum; http://www.trolleyride.org, 1910)
c1f62f5d24c7b72c14c48727e265777e
Wildwood Park on the southeast shore of Lake Minnetonka offered a wide variety of amusements for the public, including this pavilion.
United States
Minnesota
Washington
Mahtomedi
Mode of access: Internet.
Keywords: streetcars; Twin City Rapid Transit Co.; street scene; Transportation